2011
DOI: 10.1186/1743-422x-8-141
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of antiviral and virucidal activity of a high molecular weight hyaluronic acid

Abstract: Backgroundhyaluronic acid (HA), a non-sulphated glycosaminoglycan, is present in synovial fluid, vitreous humour serum and many connective tissues. Pharmaceutical preparations of HA are used in clinical practice for wound healing, joint pain, kerato-conjunctivitis, asthma, mouth care, oesophageal-reflux, and gastritis. Moreover, it is used as a filler to counteract ageing and facial lipoatrophy. Our study aims at investigating the in vitro antiviral activity of a high molecular weight HA.Methodsthe MTT test wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 20 publications
3
29
0
Order By: Relevance
“…Wang et al [24] demonstrated that chlorogenic acid possessed a substantial inhibitory activity against HBV-DNA replication. Coxsackievirus B5 and herpes simplex virus-1 replication were consistently inhibited by hyaluronic acid, regardless of the time of addition [4]. Our previous study also demonstrated that sodium tanshinone IIA sulfonate could inhibit PRRSV replication during a single replication cycle [23].…”
Section: Fig 4 Effects On the Antiviral Activities Of Adding Two Cosupporting
confidence: 51%
“…Wang et al [24] demonstrated that chlorogenic acid possessed a substantial inhibitory activity against HBV-DNA replication. Coxsackievirus B5 and herpes simplex virus-1 replication were consistently inhibited by hyaluronic acid, regardless of the time of addition [4]. Our previous study also demonstrated that sodium tanshinone IIA sulfonate could inhibit PRRSV replication during a single replication cycle [23].…”
Section: Fig 4 Effects On the Antiviral Activities Of Adding Two Cosupporting
confidence: 51%
“…The antiviral efficiency of CD‐PAM‐ co ‐GPHMG reached to 96.2% at a concentration of 50 ppm. Hyaluronic acid (HA) and anionic or cationic dendrimers have shown antiviral activities against a wide spectrum of viruses, e.g., HSV, coxsackievirus, influenza virus, by blocking the virion's attachment to target cells. However, these antiviral agents were ineffective for ADV .…”
Section: Resultsmentioning
confidence: 99%
“…Hyaluronic acid (HA) and anionic or cationic dendrimers have shown antiviral activities against a wide spectrum of viruses, e.g., HSV, coxsackievirus, influenza virus, by blocking the virion's attachment to target cells. However, these antiviral agents were ineffective for ADV . It is obvious that the polymer can be used as potent virucidal agents against ADV below their toxic concentration to mammalian cells.…”
Section: Resultsmentioning
confidence: 99%
“…Medical uses of hyaluronic acid include wound healing and mouth care, as well as the treatment of conditions such as joint pain, kerato-conjunctivitis, asthma, and gastritis. This compound, in addition, displays antiviral activity against a variety of DNA and RNA viruses [201]. But, despite its positive effects, the fact that hyaluronic acid could enhance blood-brain barrier permeability, either transcellularly, paracellularly or through infected phagocytes [202], considerably limits its medical uses.…”
Section: Antivirals From Fungimentioning
confidence: 99%